REGULATION AND PUBLIC POLICIES OF SOCIAL AND SOLIDARITY ECONOMY - Cirino, Caio Nordi Jorge Armani; Randi, Luciana Teixeira; Rubbo, Thiago de Mello Almada (Seven Editora, 2026)
The present study aims to investigate the regulation process of Social and Solidarity Economy in Brazil, primarily from the perspective of public policies. In this sense, the aim was to demonstrate that the regulation of Social and Solidarity Economy through public policies is a sociopolitical process resulting from the constant interaction, within public spaces, between civil society actors and the State. The current institutional context in Brazil indicates a still fragile and nascent regulation, largely attributed to the inherent weaknesses in the modus operandi of Solidarity Economic Enterprises. It has been shown that a viable alternative to addressing these weaknesses is the strengthening of an entrepreneurial ecosystem for SSE. Furthermore, efforts were made to delineate some international experiences in favor of regulating Social and Solidarity Economy, which certainly can provide elements for the Brazilian regulatory journey. In conclusion, it is evident that the process of regulating Social and Solidarity Economy needs to advance in Brazil, particularly through the implementation of coherent and robust public policies, to give substance to the principles of social justice that characterize Social and Solidarity Economy. DOI: https://doi.org/10.56238/sevened2026.008-104